Training transfer: The interaction of changed behaviour and co-worker support on job performance / Fadzilah Mohd Shariff, Artinah Zainal and Rahmat Hashim - Mohd Shariff, Fadzilah; Zainal, Artinah; Hashim, Rahmat (UiTM Press, 2013)
The present study examined the moderating effect of changed behav-iour on the relationship between co-workers support on frontline employees job performance. The authors hypothesize that co-work-ers support are more strongly related to performance among front-line employees reporting low than high level in changed behaviour. Results of Structural Equation Modeling, gathered from 264 employ-ees who held positions as Food and Beverage outlet servers in 4 and 5 star ratings hotels, support the hypothesis. The result indicates that when frontline employees’ exhibit low changed behaviour, the relationships between co-worker support and job performance are stronger. Implications for substantive research, strengths and limita-tions, and directions for future research are offered.